2012
DOI: 10.1017/s0950268812001665
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and clinical manifestations of human cryptosporidiosis in Sweden

Abstract: This study describes the epidemiology and symptoms in 271 cryptosporidiosis patients in Stockholm County, Sweden. Species/genotypes were determined by polymerase chain reaction-restriction fragment-length polymorphism (PCR-RFLP) of the Cryptosporidium oocyst wall protein (COWP) and 18S rRNA genes. Species were C. parvum (n=111), C. hominis (n=65), C. meleagridis (n=11), C. felis (n=2), Cryptosporidium chipmunk genotype 1 (n=2), and a recently described species, C. viatorum (n=2). Analysis of the Gp60 gene reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
104
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(123 citation statements)
references
References 47 publications
15
104
2
2
Order By: Relevance
“…pig genotype II (isolated from pigs in China), C. parvum (Egyptian isolate from buffalo in Ismailia province) and C. baileyi (isolated from quails in China). Despite that these results disagree with McLauchlin et al (2000) and others (Insulander et al, 2013;Friesema et al, 2012;Wang et al, 2011) who could identify C. parvum genotypes by 18S rRNA gene sequence, they confirmed the previous conclusion of many researchers who found the use of multi-loci analysis had better results with regards to Cryptosporidium genotyping (Abe and Teramato, 2012;Amer et al, 2010). Because their sequences had higher intraspecific variation than the ribosomal RNA gene regions (Morgan et al, 1999b), it was suggested that other Cryptosporidium genes targets should be used for amplification including the Cryptosporidium oocyst wall protein (COWP), 16S rRNA, Hsp70, Actin, β-Tubulin, gp60, microsatellites, minisatellites and extrachromosomal double-stranded RNA (Xiao et al, 2004;Caccio et al, 2005;Coklin et al, 2007).…”
Section: Discussioncontrasting
confidence: 80%
“…pig genotype II (isolated from pigs in China), C. parvum (Egyptian isolate from buffalo in Ismailia province) and C. baileyi (isolated from quails in China). Despite that these results disagree with McLauchlin et al (2000) and others (Insulander et al, 2013;Friesema et al, 2012;Wang et al, 2011) who could identify C. parvum genotypes by 18S rRNA gene sequence, they confirmed the previous conclusion of many researchers who found the use of multi-loci analysis had better results with regards to Cryptosporidium genotyping (Abe and Teramato, 2012;Amer et al, 2010). Because their sequences had higher intraspecific variation than the ribosomal RNA gene regions (Morgan et al, 1999b), it was suggested that other Cryptosporidium genes targets should be used for amplification including the Cryptosporidium oocyst wall protein (COWP), 16S rRNA, Hsp70, Actin, β-Tubulin, gp60, microsatellites, minisatellites and extrachromosomal double-stranded RNA (Xiao et al, 2004;Caccio et al, 2005;Coklin et al, 2007).…”
Section: Discussioncontrasting
confidence: 80%
“…To the best of our knowledge, this is the first report of this subtype in sheep. Subtype IIaA16G1R1 has a wide geographic distribution (Xiao, 2010;Robertson et al, 2014) and has recently been detected in calves and humans in Sweden (Insulander et al, 2013;Silverlås et al 2010Silverlås et al , 2013, in humans in Canada (Iqbal et al, 2015), Australia (Koehler et al, 2014), Estonia (Lassen et al, 2014) and Mexico (Valenzuela et al, 2014), dairy cattle in Argentina (Del Coco et al, 2014) and sheep and cattle in Romania (Imre et al 2011;Imre et al, 2013). This subtype of C. parvum also caused an outbreak in Sweden through direct contact between calves and humans (Kinross et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Less common species include Cryptosporidium meleagridis. In Sweden, C. meleagridis is possibly the third most common species associated with human cryptosporidiosis and accounted for about 6% of the cases in a recent study, all representing imported cases (5). In some parts of the world, C. meleagridis may even be as common as C. parvum (6)(7)(8)(9).…”
mentioning
confidence: 99%